(untitled) - Jackson, Jack (Camden, Me., 2005)
From basic diving certification topics and techniques to advanced technical diving, Complete Diving Manual has everything you need—all in full, stunning color. Whether you're an experienced diver or haven't yet gotten your C-card, your passport to diving expeditions is here, including: Choosing, using, maintaining, and storing equipment. Basic training, from pool to open water. Diving physiology, including buoyancy, behavior of gases, the bends, and hypothermia...
Keywords: Deep diving,Lặn sâu